(untitled) (Abuja Journal of Sociological Studies, 2026)
The research investigates the lived realities of residents whose lives have been directly or indirectly affected, this desk-based study explores the paradoxical and deeply human dimension of “victimless crimes” that tragically escalate into homicide cases within the Kano Metropolitan Area of Nigeria. Drawing on a rich array of secondary dataincluding academic literature, media reports, court records, and Non-governmental Organization (NGO) publications the research investigates the lived realities of residents whose lives have been directly or indirectly shattered by minor infractions that turned deadly. By re-evaluating the notion of victimlessness through the lens of systemic inequality, institutional failure, and socio- economic deprivation, this study reveals the silent suffering of individuals and families who are often overlooked in criminal justice narratives. Anchored in Structural Strain Theory, the paper exposes how ordinary people seeking survival in informal economies or navigating unjust systems become unintended victims of violence, state neglect, or community retribution. The findings urge a reconceptualization of crime and justice in urban Nigeria, calling for compassionate policy reforms that prioritize dignity, protection, and equity for all residents, especially those rendered invisible by the very laws meant to protect them.